Effectiveness of the Malaria Control Program at Buana Clinic, Yohanis Kapiau Air Force Base, Mimika Regency - Chaerul Dinata; Izzatusholekha Izzatusholekha; Maya Puspita Dewi (Jurnal Syntax Transformation, 2026)
This qualitative descriptive-analytical study examines the role of Buana Clinic at Yohanis Kapiyau Air Force Base (Lanud YKU) in malaria prevention, diagnosis, and treatment in Mimika Regency, a high-endemic area for malaria. The study focuses on service quality challenges (Reliability and Responsiveness) and the hybrid collaboration model. Data were collected through triangulation methods: observation, in-depth interviews with key stakeholders, and clinical documentation. The findings reveal that the Prevention Pillar, supported by the Civil-Military Cooperation (CIMIC) strategy, effectively implements vector control and net distribution interventions. However, the Diagnosis and Treatment Pillar faces significant challenges, with a high surge in malaria cases and a shortage of healthcare personnel, compromising Responsiveness and the critical 14-day follow-up treatment, jeopardizing clinical Reliability. The Hybrid Collaboration Model plays a critical role in managing the internal military population but needs further manpower support to sustain malaria elimination efforts. The study concludes that enhancing the internal curative capacity at Buana Clinic is essential to accelerate malaria elimination in Mimika.